CONTROL OF NANOLIQUID THERMAL CONVECTION WITH COMBINED EFFECTS OF ROTATION, MAGNETIC FIELD, AND POROUS OBJECT IN A CYLINDRICAL CAVITY - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Sheremet, Mikhail A. (Begell House Inc, 2022)
In this study, convective heat transfer performance under the coupled effects of magnetic field, rotations, and natural convection are analyzed by using a porous object in a cylindrical cavity. Finite element method analysis is considered for the range of parameters: permeability of the object (Darcy number: 10-4 < Da < 10-1), Rayleigh number (Ra: 105 < Ra < 8 x 105), rotational Reynolds number (Rem,: 0 < Rem, < 2000), strength of magnetic field (Hartmann number: 0 < Ha < 25) and aspect ratio of the porous object (AR: 0.5 < AR < 2. Water-Ag/MgO hybrid nanofluid is used. It is observed that thermal performance is improved when rotations become active. For an object with lower permeability at the highest speed, the amount of increment becomes 137%. The average Nu rises with higher permeability while increasing the aspect ratio of the object reduces the heat transfer at lowest permeability. When rotations become active, the impacts of magnetic field on the heat transfer reduction becomes less while 48.5% reduction of average Nusselt number is obtained without rotations. Proper orthogonal decomposition method is used for thermal field and performance estimations by using 12 modes for the fluid domain and 4 modes for porous regions.
Keywords: natural convection; rotations; magnetic field; hybrid nanofluid; finite element method; proper orthogonal decomposition